GEOGRAPHIC AND ECOLOGICAL AMPLITUDE IN THE NECTARIVOROUS BAT ANOURA FISTULATA (PYHLLOSTOMIDAE: GLOSSOPHAGINAE) (2014)
The wide range of feeding habits among phyllostomid bats has resulted in the selection of unique and contrasting morphological attributes. It has been suggested that nectarivorous bat species co-evolve with the plants they use as primary source of food, and changes in morphology and behavior in the bat, are in some way directed by changes in morphology and phenological cycles of the plants. The nectarivorous bat Anoura fistulata (Pyhllostomidae: Glossophaginae) has the longest tongue in proportion to body size among mammals; feature that apparently allows the species to take nectar from flowers with long corollas, some of them typical of highland ecosystems. In spite of this unique morphological adaptation, little is known on the ecological requirements of the species. Herein, Geographic Information System-based analyses and niche modeling techniques were applied to investigate the geographic and ecological niche breath of A. fistulata. We also introduce the first Bolivian record of the species collected at Hernando Siles, Department of Chuquisaca (20°10’0.0’’ S, 64°15’0.00’’ W, at 1,524 m), which represents a remarkable extension in the distribution of the species of more than 7°. Our analyses revealed that A. fistulata occurs in contrasting ecosystems, from Andean montane and pre-montane moist forest in Western Ecuador and Central Colombia, up to arid and semiarid environments in southern Colombia and Bolivia. Anoura fistulata occurs across a wide elevational range between 1,175 and 2,510 m, which is well represented along the geologic unit of the Batholith of Ecuador. A constriction of this elevational belt along the Peruvian Punas and Yungas was suggested as a natural barrier for the establishment of A. fistulata. The Peruvian Punas and Yungas isolate A. fistulata of Bolivia from records in the northern range of the distribution of the species.